2006
DOI: 10.2337/db06-0220
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Eucaloric High- and Low-Sucrose Diets With Identical Macronutrient Profile on Insulin Resistance and Vascular Risk

Abstract: The long-term impact of dietary carbohydrate type, in particular sucrose, on insulin resistance and the development of diabetes and atherosclerosis is not established. Current guidelines for the healthy population advise restriction of sucrose intake. We investigated the effect of high-versus low-sucrose diet (25 vs. 10%, respectively, of total energy intake) in 13 healthy subjects aged 33 ؎ 3 years (mean ؎ SE), BMI 26.6 ؎ 0.9 kg/m 2 , in a randomized crossover design with sequential 6-week dietary interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 46 publications
5
80
0
Order By: Relevance
“…Excessive intake of sucrose, glucose, and fructose from fruit juices is thought to contribute to the development of diabetes and obesity (5)(6)(7)(8). We propose here that fermenting juices using lactic acid bacteria may solve this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive intake of sucrose, glucose, and fructose from fruit juices is thought to contribute to the development of diabetes and obesity (5)(6)(7)(8). We propose here that fermenting juices using lactic acid bacteria may solve this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also varied with respect to the composition of the basic and intervention diets, which might have influenced the results. For example Black et al (2006) found that a high-sucrose diet (25 E%) resulted in increases in total and LDL cholesterol by 15% and 24%, respectively, compared to the control diet (10 E% sucrose). The authors hypothesise that the higher level of SFA and lower level of PUFA in the high-sucrose diet could have contributed to the cholesterol-raising effect.…”
Section: Serum Lipidsmentioning
confidence: 99%
“…The previous long-standing antipathy to sucrose was reinforced during the 1980s by a series of studies suggesting that sucrose aggravated hyperglycaemia and dyslipidaemia. However, later reports cast doubt on these findings, with studies including more subjects and of longer duration; sucrose intakes of up to 200 g/day did not demonstrate such deleterious effects and influenced the decision to relax the recommendations (Abraira & Derler 1988;Bantle, Laine, & Thomas 1986;Black et al 2006;Jellish, Emanuele, & Abraira 1984).…”
Section: Introductionmentioning
confidence: 97%